2015
DOI: 10.1016/j.jscs.2015.06.001
|View full text |Cite
|
Sign up to set email alerts
|

Visible light induced degradation of methyl orange using β-Ag0.333V2O5 nanorod catalysts by facile thermal decomposition method

Abstract: Visible light induced degradation of methyl orange using β -Ag 0.333 V 2 O 5 nanorod catalysts by facile thermal decomposition method, Journal of Saudi Chemical Society (2015), doi: http://dx.Abstract One dimensional nanorods of β-Ag 0.333 V 2 O 5 have been synthesized by facile thermal decomposition method without using any additives. The prepared sample was characterized by different physical and chemical techniques such as XRD, FE-SEM, TEM, DRS and XPS. The photocatalytic activity of β-Ag 0.333 V 2 O 5 cata… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(27 citation statements)
references
References 30 publications
(34 reference statements)
0
27
0
Order By: Relevance
“…Therefore, the temperatures higher than 60 o C was not studied (Figure 7). This study indicated that the degradation of MO is thermally achievable [23].…”
Section: Bulletin Of Chemical Reaction Engineering and Catalysismentioning
confidence: 68%
“…Therefore, the temperatures higher than 60 o C was not studied (Figure 7). This study indicated that the degradation of MO is thermally achievable [23].…”
Section: Bulletin Of Chemical Reaction Engineering and Catalysismentioning
confidence: 68%
“…At pH higher than 6, the adsorbent surface charge turned to negative, the DOC molecules were mainly in anionic form and hence the adsorption capacity significantly decreased (Saravanan et al . ). The data related to the previously studied adsorbents collected in Supporting Information Table S2 indicated that depending on the surface charge of the adsorbent, the optimized pH was within pH = 4–6.…”
Section: Resultsmentioning
confidence: 97%
“…; Saleh & Gupta ; Saravanan et al . , , , ) methods have been studied. For removal of DOC from water and liquid wastes, different adsorbents such as mesoporous silica (Brigante & Avena ), black tea and pomegranate peel (Hassan & Ali ), Fe 3 O 4 (Ghaemi & Absalan ), graphene‐like layered molybdenum disulfide (Chao et al .…”
Section: Introductionmentioning
confidence: 99%
“…Now, the MNPs have been widely applied to many fields, such as water pollution , drug and gene delivery , magnetic resonance imaging , enzyme immobilization , the control of cells and cellular function , and so on. Among these, water pollution has become a global issue and attracted increasing attentions, especially the dyestuff , the heavy metal sewage , the sewage from the pharmaceutical companies , and so on. Dyes have been extensively used in textile industries, pulp mills and dyestuff manufacturing, and more than 9 million tons of highly colored dye wastewaters are produced annually , and dyes can cause severe problems such as increasing the chemical oxygen demand, delaying the growth of micro‐organisms and reducing light penetration and visibility , and the ingestion of dyes can result in a severe damage to organism, and in particular, some of the organic dyes and their products have a mutagenic or carcinogenic influence on human beings .…”
Section: Introductionmentioning
confidence: 99%